2011
DOI: 10.1209/0295-5075/94/10001
|View full text |Cite
|
Sign up to set email alerts
|

Extracting work from a single heat bath through feedback

Abstract: Work can be extracted from a single heat bath if additional information is available. For the paradigmatic case of a Brownian particle in a harmonic potential, whose position has been measured with finite precision, we determine the optimal protocol for manipulating the center and stiffness of the potential in order to maximize this work in a finite-time process. The bound on this work imposed by a generalized second law inequality involving information can be reached only if both position and stiffness of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
226
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(232 citation statements)
references
References 42 publications
5
226
1
Order By: Relevance
“…In fact, the processing of the information I by a physical device will at least offset the gain of work or decrease of total entropy that was realized in the measurement. Without entering in further details, we cite two recent works in which this informationto-work conversion is illustrated, namely one dealing with the case of a Brownian particle in a manipulated potential [39] and the other with a Hamiltonian particle [40]. Note also that a related result was derived in a different context (quantum system subject to feedback control) in [41,42], and verified for the rectification of a Brownian particle moving in a staircase potential [15] (see also [43]).…”
Section: Nonequilibrium Landauer Principlementioning
confidence: 99%
“…In fact, the processing of the information I by a physical device will at least offset the gain of work or decrease of total entropy that was realized in the measurement. Without entering in further details, we cite two recent works in which this informationto-work conversion is illustrated, namely one dealing with the case of a Brownian particle in a manipulated potential [39] and the other with a Hamiltonian particle [40]. Note also that a related result was derived in a different context (quantum system subject to feedback control) in [41,42], and verified for the rectification of a Brownian particle moving in a staircase potential [15] (see also [43]).…”
Section: Nonequilibrium Landauer Principlementioning
confidence: 99%
“…The mutual information I is positive and it is zero if and only if x and y are independent. If x is the microscopic (or mesoscopic) state of a thermodynamical system in equilibrium with a heat bath at temperature T , then the information obtained can be used to extract heat from the heat bath and convert it into work [1,2,3,7,8,9]. More precisely, let x be the microscopic state (or micro-state) of a thermodynamic system S in contact with a heat bath at temperature T and let p(x) be its equilibrium (canonical) distribution.…”
Section: Modeling the Measurement Devicementioning
confidence: 99%
“…This is not the case in general. Consider for instance the (imperfect) measurement of the position of a Brownian particle as presented in [3]: once one has measured the position of the particle, one should immediately perform a process depending on the measured position in order to convert all of the information into heat. In fact, the particle does not stop moving after the measurement.…”
Section: Relation To Landauer's Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent examples by Szilard [1] and others (for example Refs. [2][3][4][5][6]) have revealed that with feedback one can design engines that perform work by extracting energy from a single thermal bath.…”
Section: Introductionmentioning
confidence: 99%